2013
DOI: 10.7464/ksct.2013.19.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure on HCl Absorption Behaviors of a K-based Absorbent in the Fixed Bed Reactor

Abstract: 주제어 : 염화수소, 고정층반응기, K-계열 흡수제, 압력, 연소전포집 Abstract : In this study, the hydrogen chloride removal using K-based dry sorbents (K2CO3/Al2O3, KEPRI, Korea) was studied with varying the pressure in a fixed bed reactor (15 cm tall bed with 0.5 cm I.d.). Working temperature was 400℃ and feed gas concentration was 750 ppm (HCl vol%, N2 balance). The chloride sorption capacity of sorbent increases with increasing pressure (1, 5, 10, 15 and 20 bar). Also, after forming KCl crystal by reaction with K2CO3 and HCl, owing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, related researches are hardly found so far. The reaction path is as follows: K 2 CO 3 + 2HCl → 2KCl + CO 2 + H 2 O. Kim et al carried out a HCl breakthrough test using a K 2 CO 3 impregnated dry sorbent, and it was confirmed that the optimum sorption property was at the highest pressure and temperature conditions (20 bar and 400 °C) . Kim et al also reported HCl breakthrough behaviors of zeolite 13X pellet at low temperature condition .…”
Section: Introductionmentioning
confidence: 98%
“…However, related researches are hardly found so far. The reaction path is as follows: K 2 CO 3 + 2HCl → 2KCl + CO 2 + H 2 O. Kim et al carried out a HCl breakthrough test using a K 2 CO 3 impregnated dry sorbent, and it was confirmed that the optimum sorption property was at the highest pressure and temperature conditions (20 bar and 400 °C) . Kim et al also reported HCl breakthrough behaviors of zeolite 13X pellet at low temperature condition .…”
Section: Introductionmentioning
confidence: 98%